(untitled) (Journal of Management and Educational Sciences, 2025)
This study aims to deeply examine the principle of proportionality in the context of the use of force by law enforcement officers and its role in maintaining public order. The legal basis, types and areas of application of the authority to use force granted to law enforcement officers for the purpose of maintaining public order have been addressed, and in this context, important emphasis has been placed on how the authority granted to law enforcement officers is limited in line with the principles of the rule of law and human rights. The functioning of the principle of proportionality, based on the European Convention on Human Rights, has been examined in connection with examples of implementation in Turkey, and the examples of cases that arise when law enforcement officers act contrary to the principle of proportionality and their legal consequences have been analyzed. This analysis aims to comprehensively evaluate individual and administrative responsibilities in terms of the limits and responsibilities of the use of force by law enforcement officers. As a result, it has been emphasized that a balance must be established between the protection of individual rights and freedoms and the provision of justice when using state power.